FINANCIAL SERVICIES LIBERALIZATION AND INTERNATIONAL INTEGRATION IN SOUTH EASTERN EUROPE - Prica, Ivana (Economic Annals, 2008)
The first part of this paper analyses the regulatory framework for international trade in financial services within the auspices of the World Trade Organisation (WTO), with special attention paid to the open issues including the scope of prudential measures and capital mobility limitations. The process of the international integration of the South Eastern Europe (SEE) countries is mainly dictated by their goal of EU integration. With regard to the services' sectors, a major liberalisation step on the way is WTO accession. Of the countries in the region only Serbia , Bosnia and Herzegovina and Montenegro are still not WTO members and in order to become members significant liberalisation commitments will be demanded of them. For this reason the second part of the paper deals with concrete financial liberalisation commitments undertaken by the original WTO members in SEE and the newly WTO-acceded SEE member countries. The last part of the paper provides a quantitative analysis of these commitments by means of the measurement of liberalisation indices in the banking sectors in SEE countries. This is to provide a general idea of the scope of liberalisation that may be required from a SEE country in order to achieve WTO membership on the road to EU integration.